Adopting Bricolage to Overcome Resource Constraints: The Case of Social Enterprises in Rural India. (June 2019) - Hota, Pradeep Kumar; Mitra, Sumit; Qureshi, Israr
ABSTRACT: Social enterprises (SEs) primarily aim to create social value, that is, to generate benefits or reduce costs for society, while maintaining financial sustainability. Owing to their unique operating conditions and organizational characteristics, SEs face more severe resource challenges than their commercial counterparts. These challenges are exacerbated for SEs operating in emerging economies with complex social contexts. Overcoming these resource constraints and social challenges is vital for SEs to achieve their mission. Using an inductive multiple case-study approach, we identify a unique bricolage solution for achieving the dual objectives of SEs. Our findings suggest that identifying locally embedded village level entrepreneurs is a bricolage activity that social entrepreneurs leverage in the resource constrained environment of emerging economies, especially for the social enterprises that are active in the villages but were founded by social entrepreneurs who are not from these villages. This article therefore contributes to both social entrepreneurship literature as well as entrepreneurial bricolage literature and has important implications for future research and practice. 摘要: 社会企业的主要目标在于创造社会价值，即在维持财务可续性的同时，为社会创造利润或减少成本。由于社会企业独特的运营条件和组织特征，它们比商业企业遇到更为严峻的资源挑战。而在复杂社会环境下的新兴经济体中运营的社会企业，这些挑战更为严重。克服这些资源和社会挑战对社会企业实现使命至关重要。我们采用归纳性的多案例方法发现，社会企业在实现双重目标的过程中采用了一种独特的拼贴方案。我们的发现表明，找出嵌入在当地的乡村水平的企业家，是社会企业家在新兴经济的资源约束环境下可以利用的一种拼贴活动，尤其对于那些活跃在乡村但创立者又不是来自这些乡村的社会企业而言更是如此。这篇文章既对于社会企业创业和创业拼贴的文献做出了贡献，也对于未来的研究和实践具有重要意义。 АННОТАЦИЯ: Социальные предприятия (СП) в первую очередь стремятся создавать социальные блага, а именно получать выгоду или снижать затраты для общества, сохраняя при этом финансовую устойчивость. Ввиду этих уникальных условий работы и организационных особенностей, СП сталкиваются с более серьезным недостатком ресурсов, чем коммерческие предприятия. Эти проблемы усугубляются для СП, которые работают в странах с развивающейся экономикой в сложных социальных условиях. Преодоление этих ресурсных ограничений и социальных проблем жизненно необходимо для выполнения миссии СП. Используя индуктивный подход, основанный на множественных тематических исследованиях, мы находим уникальное решение бриколажа для достижения двуединых целей СП. Наши результаты показывают, что идентификация местных предпринимателей на уровне села является бриколажной деятельностью, которую социальные предприниматели используют в развивающихся странах в условиях нехватки ресурсов, особенно в случае социальных предприятий, которые работают в деревнях, но были основаны социальными предпринимателями, которые не являются выходцами из этих деревень. Таким образом, данная статья вносит свой вклад как в литературу по социальному предпринимательству, так и в литературу по бриколажу предпринимателей, а также делает важные выводы для будущих научных исследований и практической деятельности. RESUMEN: Las empresas sociales (ES) tienen como objetivo principal crear valor social, o sea, generar beneficios o reducir los costos para la sociedad, al mismo tiempo que mantienen la sostenibilidad financiera. Debido a sus condiciones únicas de operación y características de organización, las empresas sociales enfrentan desafíos de recursos más severos que sus contrapartes comerciales. Estos desafíos son exacerbados para las empresas sociales que operan en economías emergentes con contextos sociales complejos. Superar estas limitaciones de recursos y desafíos sociales es vital para que las empresas sociales logren su misión. Usando un enfoque de estudio de caso múltiple inductivo, identificamos una solución de bricolaje única para lograr los objetivos duales de las empresas sociales. Nuestros hallazgos sugieren que la identificación de emprendedores a nivel de aldea localmente insertados es una actividad de bricolaje que los emprendedores sociales apalancan en el entorno de recursos limitados de las economías emergentes, especialmente para las empresas sociales que están activas en las aldeas pero que fueron fundadas por emprendedores sociales que no son de estas aldeas. Este artículo por lo tanto contribuye tanto a la literatura de emprendimiento social como a la literatura de bricolaje empresarial y tiene implicaciones importantes para la investigación y la práctica futuras.